Value of cyst localization to predict cystobiliary communication in patients undergoing conservative surgery with hydatid cyst - Alan B; Kapan M; Teke M; Hattapoğlu S; Arıkanoğlu Z (Dove Medical Press, 2016)
Bircan Alan,1 Murat Kapan,2 Memik Teke,1 Salih Hattapoğlu,1 Zülfü Arıkanoğlu2 1Department of Radiology, 2Department of General Surgery, Faculty of Medicine, Dicle University, Diyarbakır, Turkey Objective: The objectives of this study were to investigate the relationship between the segmental localization of liver hydatid cyst by computed tomography (CT) and the presence of cystobiliary communication (CBC) and to identify the risk factors for CBC.Patients and methods: One hundred and eleven of 163 patients who underwent liver hydatid surgery between January 2011 and September 2014 were included in this study and analyzed retrospectively. The size, number, stage, and segmental and lobar localization of the cysts were investigated by CT. The presence of CBC and preoperative laboratory findings were recorded from operation notes. Results: CBC was more frequent in single large cysts. CBC was most commonly detected in segment 1 (50%), 8 (48.3%), 7 (41.2%), and 4 (40%). CBC was more frequent in the right lobe (40.4%) and Gharbi stage 3 (41.8%) and 4 (55.6%) lesions. There were no differences in CBC according to distance from the hilus. In addition, preoperative total bilirubin, direct bilirubin, alkaline phosphatase (ALP), and gamma-glutamyl transferase (GGT) elevations were associated with higher CBC frequency (P<0.05). Cyst diameter, number of cysts, and ALP and GGT elevations were independent predictors of CBC presence.Conclusion: The evaluation of hydatid cyst diameter, morphological stage, and segmental and lobar localization by abdominal CT and measurement of preoperative cyst diameter, number of cysts, and ALP and GGT values may predict the presence of CBC. Keywords: hydatid cyst, computed tomography, hydatid cyst localization, cystobiliary communication